Efforts to Revitalize Student Learning Motivation After the COVID-19 Pandemic - Dedi Riyan Rizaldi; Muhamad Zaenudin; Ziadatul Fatimah; Asep L Hamdun Ahmad; Heru Setiawan; Aris Doyan; Muh. Makhrus (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2022)
Abstract This study aims to regenerate and increase students' learning motivation after experiencing a long learning process from home due to the impact of the COVID-19 pandemic through Training for Leaders and Herbalists (TRALIS). This study uses a qualitative approach, namely the type of field research (Field Research) by focusing on the observation method. The object of this research is all students of class XII in the Department of Religion at Madrasah Aliyah Plus Nurul Islam Sekarbela with a total of 31 students. Based on the activities that have been carried out, Training for Leaders and Herbalists (TRALIS) is one form of positive activity that is very important given to students to revive enthusiasm for participating in teaching and learning activities in madrasas. This activity provides many new changes for students during the learning process including students having a strong sense of desire to participate in every activity carried out, increasing self-confidence which is seen through the attitude of students who are not afraid to appear in front of the class and express opinions during the class discussion process. Keywords: Post COVID-19 Pandemic, Learning motivation, Training for Leaders and Herbalists (TRALIS)